If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 4x) = 153 (3 * 3 + 4x * 3) = 153 (9 + 12x) = 153 Solving 9 + 12x = 153 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 12x = 153 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = 153 + -9 12x = 153 + -9 Combine like terms: 153 + -9 = 144 12x = 144 Divide each side by '12'. x = 12 Simplifying x = 12
| -5(6d-9.5)=-18.5 | | 5x+4=5x-8 | | 4p=2p+7 | | n-3/2=n-7/4 | | 8c-18=20 | | -4+4x=-1226x | | (100-x)/x=1.15 | | 13=17-5a | | 29-5q=22 | | 14=4n+5 | | 10m+8=21 | | 5(e+1)=3(2e-1) | | m^2+25m=0 | | 4(3x-2)+3(x+1)=100 | | 3p-4=10 | | 3x+2=42 | | x(x+2)=159+6(x+x+2) | | 8=3x^2-2x | | 8=3x*3x-2 | | X=3+0.25x | | X=3+0.25 | | 3Q=2P-M | | 2x-4u-5=0 | | (343)1/4(343)-1/12 | | 3(2p-7)=4p-5 | | f(-3)=-3 | | 8X+14=38+2x | | 8X+14=38+2 | | h^2-2h=0 | | 2x+3=10-3x | | 1/2X7 | | 10x-4=5x+15 |